2012
DOI: 10.1177/1934578x1200701118
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Antioxidative, Antileukemic and Anti-MMPs Activity ofEleutherococcusSpecies Cultivated in Poland

Abstract: The content of phenols (TPC), and the antioxidative, antileukemic and anti-MMPs properties of Eleutherococcus spp. cultivated in Poland are reported. The highest TPC was found in the spring leaves (20.3-37.2 mg/g). The spring leaves and roots of E. divaricatus had the strongest anti-DPPH activity (EC 50 1.2 and 1.2 mg/mL), whereas the greatest ability of iron (II) chelating was shown by autumn leaves of E. setchuensis (EC 50 0.3 mg/mL), and the ethanolic extract of E. gracilistylus roots showed the strongest l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…Załuski et al [8] reported on the TPC in the 75% ethanolic extracts from the spring leaves (20.3 to 37.2 mg/g), fresh fruits (6.1–19.7 mg/g), and roots (6.9–10.6 mg/g). In addition to this, the content of TPC and TFC in the fruits is not changed during a storage at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Załuski et al [8] reported on the TPC in the 75% ethanolic extracts from the spring leaves (20.3 to 37.2 mg/g), fresh fruits (6.1–19.7 mg/g), and roots (6.9–10.6 mg/g). In addition to this, the content of TPC and TFC in the fruits is not changed during a storage at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The ethanol extracts from roots and spring and autumn leaves revealed the IC 50 values at concentrations 208, 312, and 299  μ g/mL towards HL-60. In turn, the chloroform extract from the roots (IC 50 2.8  μ g/mL), the ethanol extracts from the roots (134.7  μ g/mL), the spring leaves (199.7  μ g/mL), the fresh fruits (331.2  μ g/mL), and the dried fruits (274.4  μ g/mL) affected Jurkat 45 leukemia cell line [8, 38]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations